Factors Associated with Mild Traumatic Brain Injury in Veterans and Military Personnel: A Systematic Review. (5th February 2014) - O'Neil, Maya E.; Carlson, Kathleen F.; Storzbach, Daniel; Brenner, Lisa A.; Freeman, Michele; Quiñones, Ana R.; Motu'apuaka, Makalapua; Kansagara, Devan
Abstract A history of mild traumatic brain injury (mTBI) is common among military members who served in Operations Enduring Freedom, Iraqi Freedom, and New Dawn (OEF/OIF/OND). We completed a systematic review to describe the cognitive, mental health, physical health, functional, social, and cost consequences of mTBI in Veteran and military personnel. Of 2668 reviewed abstracts, the 31 included studies provided very low strength evidence for the questions of interest. Cognitive, physical, and mental health symptoms were commonly reported by Veterans/military members with a history of mTBI. On average, these symptoms were not significantly more common in those with a history of mTBI than in those without, although a lack of significant mean differences does not preclude the possibility that some individuals could experience substantial effects related to mTBI history. Evidence of potential risk or protective factors moderating mTBI outcomes was unclear. Although the overall strength of evidence is very low due to methodological limitations of included studies, our findings are consistent with civilian studies. Appropriate re-integration services are needed to address common comorbid conditions, such as treatment for post-traumatic stress disorder, substance use disorders, headaches, and other difficulties that Veterans and members of the military may experience after deployment regardless of mTBI history. (JINS, 2014, 20, 1–13)